Cytotoxicity and Genotoxicity Assessment of Sandalwood Essential Oil in Human Breast Cell Lines MCF-7 and MCF-10A - Ortiz, Carmen (Evid Based Complement Alternat Med, 2016)
Sandalwood essential oil (SEO) is extracted from Santalum trees. Although α-santalol, a main constituent of SEO, has been studied as a chemopreventive agent, the genotoxic activity of the whole oil in human breast cell lines is still unknown. The main objective of this study was to assess the cytotoxic and genotoxic effects of SEO in breast adenocarcinoma (MCF-7) and nontumorigenic breast epithelial (MCF-10A) cells. Proteins associated with SEO genotoxicity were identified using a proteomics approach. Commercially available, high-purity, GC/MS characterized SEO was used to perform the experiments. The main constituents reported in the oil were (Z)-α-santalol (25.34%), (Z)-nuciferol (18.34%), (E)-β-santalol (10.97%), and (E)-nuciferol (10.46%). Upon exposure to SEO (2–8 μg/mL) for 24 hours, cell proliferation was determined by the MTT assay. Alkaline and neutral comet assays were used to assess genotoxicity. SEO exposure induced single- and double-strand breaks selectively in the DNA of MCF-7 cells. Quantitative LC/MS-based proteomics allowed identification of candidate proteins involved in this response: Ku70 (p = 1.37E − 2), Ku80 (p = 5.8E − 3), EPHX1 (p = 3.3E − 3), and 14-3-3ζ (p = 4.0E − 4). These results provide the first evidence that SEO is genotoxic and capable of inducing DNA single- and double-strand breaks in MCF-7 cells.